(untitled) (Balneo and PRM Research Journal, 2024)
Background: The idiopathic ventricular outflow tract arrhythmias may arise either from the right ventricular outflow tract or the left ventricular outflow tract. It is paramount to establish the precise location, based on the 12 lead ECG, to recommend the proper treatment for the patients. Methods: Based on the 12 lead ECG evaluation, the origin of the arrhythmias was established to be either in the RVOT or LVOT. The level of physical activity, gender, and sex were noted for each patient. Further, we evaluated the accuracy of the arrhythmia’s location based on ECG versus the patient characteristics described earlier. Results: The clinical score based on these parameters presented a 71% sensitivity level and, 69% specificity level. The overall accuracy of predicting the right versus left outflow tract origin of arrhythmias based on the QRS morphology in lead V1 and the subsequent R wave transition in the precordial leads was 96.72%, with a 100% sensitivity and 88.89% specificity. Conclusion: Our clinical score, encompassing older age, sedentarism, and hypertension for the prediction of OT origin presents a lower sensitivity and specificity when compared to the ECG for differentiating the right versus left OT arrhythmias.